The intestinal vitamin D receptor in inflammatory bowel disease: inverse correlation with inflammation but no relationship with circulating vitamin D status. (January 2019) - Garg, Mayur; Royce, Simon G.; Tikellis, Chris; Shallue, Claire; Sluka, Pavel; Wardan, Hady; Hosking, Patrick; Monagle, Shaun; Thomas, Merlin; Lubel, John S.; Gibson, Peter R.
Background: The intestinal vitamin D receptor (VDR) remains poorly characterized in patients with inflammatory bowel disease (IBD). Methods: Colonoscopic biopsies and intestinal resection specimens from the terminal ileum, ascending and sigmoid colon, from patients with and without IBD, were analyzed for VDR mRNA quantification by polymerase chain reaction, and protein localization and semi-quantification by immunohistochemistry. The relationship between VDR and intestinal inflammation, serum 25(OH)D and oral vitamin D intake was elicited. Results: A total of 725 biopsies from 20 patients with Crohn's disease (CD), 15 with ulcerative colitis (UC) and 14 non-IBD controls who underwent colonoscopy were studied. VDR gene expression and protein staining intensity was similar across all three groups, and across the intestinal segments. Sigmoid colon VDR mRNA expression inversely correlated with faecal calprotectin ( r = −0.64, p = 0.026) and histological score ( r = −0.67, p = 0.006) in UC, and histological score ( r = −0.58, p = 0.019) in patients with CD. VDR staining intensity was higher in quiescent than diseased segments. No relationship with serum 25(OH)D or oral vitamin D intake was noted. Immunohistochemical staining of 28 intestinal resection specimens from 15 patients (5 each with CD, UC and non-IBD controls) showed diffuse VDR staining in the mucosa, submucosa and circular muscle. Conclusions: VDR transcript expression and protein staining intensity are inversely related to inflammation in IBD, but unrelated to serum 25(OH)D, and similar to non-IBD controls. Strategies to upregulate intestinal VDR, potentially translating to modulation of disease activity, require investigation.